Landslide risk spatial identification in the municipality of utlan of Navarro, Jalisco, Mexico - González-Bolaños, Fátima (2023)
The municipality of Autlán presents problems of land use change and erosion that favor landslides. Spatial identification of these phenomena (5 risk classes) shows that 3 localities are located in high and very high risks areas (Autlán, Ahuacapán and Mezquitán), mainly due to the influence  of Regosol soils, annual and maximum precipitation in 24 hours with a statistically significant relationship of P < 0.05, R2 = 0.99, 0.66 and 0.86. Landslides represent a risk for infrastructure and the population, finding a significant relationship (α = 0.001) between the number of houses and population density per locality only for regular to high threat to landslide. In the absence of land use planning by the municipality, attention and remediation activities are proposed, mainly in urban areas located in landslide-sensitive structures, taking into account the results obtained